2014
DOI: 10.1155/2014/651593
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Essential Oils Loaded in Nanosystems: A Developing Strategy for a Successful Therapeutic Approach

Abstract: Essential oils are complex blends of a variety of volatile molecules such as terpenoids, phenol-derived aromatic components, and aliphatic components having a strong interest in pharmaceutical, sanitary, cosmetic, agricultural, and food industries. Since the middle ages, essential oils have been widely used for bactericidal, virucidal, fungicidal, antiparasitical, insecticidal, and other medicinal properties such as analgesic, sedative, anti-inflammatory, spasmolytic, and locally anaesthetic remedies. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
254
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 351 publications
(295 citation statements)
references
References 69 publications
5
254
1
17
Order By: Relevance
“…Despite the activity observed with the bioassays that we have conducted, the therapeutic outcome of these flavonoids/its enriched active fractions in the in vivo system is still limited due to its physicochemical nature of poor water solubility, deprived intestinal absorbance, and limited bioavailability. 40,41 To overcome this obstacle, numerous attempts of delivery systems for individual flavonoids have been established such as phytosome/liposome. 42 However, previous reports indicated that isolation and purification of the bioactive constituents result in lessening of pharmacological activities that were Figure 4 Antioxidant activity of MO bioactive fractions.…”
mentioning
confidence: 99%
“…Despite the activity observed with the bioassays that we have conducted, the therapeutic outcome of these flavonoids/its enriched active fractions in the in vivo system is still limited due to its physicochemical nature of poor water solubility, deprived intestinal absorbance, and limited bioavailability. 40,41 To overcome this obstacle, numerous attempts of delivery systems for individual flavonoids have been established such as phytosome/liposome. 42 However, previous reports indicated that isolation and purification of the bioactive constituents result in lessening of pharmacological activities that were Figure 4 Antioxidant activity of MO bioactive fractions.…”
mentioning
confidence: 99%
“…A nanotechnology approach could be attractive in modulating both drug pharmacokinetics and biodistribution, thus decreasing potential side effects by leaving the normal sensitive cells unharmed. Additionally, nanovectors could mask unpleasant taste or limit the volatility of a molecule/extract (i.e., essential oil) [16,17].…”
Section: Nanomedicine: Merely a Question Of Size?mentioning
confidence: 99%
“…Encapsulation in nanometric particles is an alternative for overcoming these problems but, additionally, due to the subcellular size, may increase the cellular absorption mechanisms and increase bioefficacy, as reported in a comprehensive recent review [17].…”
Section: Nanocarriers Loaded With Essential Oils To Optimize Their Thmentioning
confidence: 99%
“…However, the essential oils are limited for the application due to highly unstable, volatile, and insoluble in water. [9][10] Thixogel, a unique thixotropic gel properties which can be liquid when stirred or shaken, has been developed as a novel gel formulation for topical drug delivery, especially for hydrophobic plant actives. 11 The thixogel technology has many advantages, such as a soft oil-in-water emulsion, a quick drying emulsion on the skin, a stable emulsion without the addition of surfactants that can irritate the skin, such as alcohols and fatty acid esters.…”
Section: Introductionmentioning
confidence: 99%